STUDENT-TEACHERS’ PERCEPTIONS OF THE EDUCATIONAL ENVIRONMENT AT PHNOM PENH TEACHER EDUCATION COLLEGE (PTEC): A DREEM-BASED STUDY: Student-Teachers’ Perceptions on Surrounding Environment Teaching and Learning of Phnom Penh Teacher Education College (PTEC) - Phearun Reth; Sophea Seng; Chanvey Kun; Kimsron Srieng (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Phnom Penh Teacher Education College (PTEC) is well-known as an institution in Cambodia and it is the first instituute that establish to promote teachners’ qualification and teaching quality. This study aimed to explore how the surrounding environment at Phnom Penh Teacher Education College (PTEC) affected student-teachers' perception of their learning and teaching. The instrument in this study was used questionnaire, which adapted from the previous relevant topic. Likert scale was utilized to evaluate 207 individuals who were student-teachers. Utilizing five DREEM domains of gender, accommodation, and qualification. The result revealed that there were no differences in the student’s perspective. Students claimed that the surrounding environment was acceptable in total. Researcher strongly recommend DREEM instrument to assess the surrounding environment in the university or college because it may be helpful to address and deal with this particular problem. The further research should focus on lecturers who work there to illustrate their perspective on surrounding environment at PTEC.